Exploring the Impacts of Learning Styles on Collaboration in Project-Based Learning across Gender - Aprianto, Dedi; Sutarman, Sutarman; Syarifaturrahman, Wahyu Kamil (Humanitatis : Journal of Language and Literature, 2025)
The study investigates the impact of learning styles on collaboration in Project-Based Learning (PjBL) across gender and how these styles affect their collaborative behaviors in PjBL. Addressing a significant gap in understanding how these factors interact in collaborative educational contexts. The research aims to determine whether there are significant differences in learning styles and collaboration based on gender and how these styles influence collaborative behaviors. Using a mixed-method explanatory sequential design, the study involved 160 participants from the Computer Science and 35 from the Nutrition departments, with quantitative data analyzed using Two-Way ANOVA and qualitative insights gathered from 35 interviews across all classes. The findings reveal that male students tend to outperform in visual learning styles, while female students perform better in auditory learning contexts. Qualitative data further highlighted the importance of gender-responsive instructional strategies for enhancing teamwork effectiveness. In conclusion, the study highlights that integrating diverse learning styles into pedagogical practices fosters inclusivity and improves learning outcomes. It advocates adaptive teaching approaches that accommodate diverse cognitive needs, ultimately contributing to more effective collaborative learning experiences across diverse educational environments.